2020
DOI: 10.1371/journal.pntd.0008823
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of two-year mortality among HIV positive patients with Cryptococcal meningitis initiating standard antifungal treatment with or without adjunctive dexamethasone in Uganda

Abstract: Globally, early initiation of antiretroviral therapy for HIV led to a reduction in the estimated mortality from cryptococcal meningitis (CCM) from 624,700 in 2009 to 181,100 in 2014. However, CCM remains one of the leading causes of mortality among HIV infected patients especially in sub-Saharan Africa where 75% of the deaths occur. Most of the studies evaluating mortality have reported short-term mortality (at or before 10 weeks of therapy). We determined mortality and associated factors among patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…difference in mortality between males and females, similar to an earlier study conducted in Uganda [28]. Even in the interventional CryptoDex trial in Uganda and Asia, a similar trend of sub-optimal long-term survival was observed, with mortality of 60% at 2 years among HIV patients with CM [29,30]. Conversely, an earlier study in Uganda observed a 5-year survival rate of 42% among 189 CM patients which is higher compared to our study [11].…”
Section: Plos Onesupporting
confidence: 87%
“…difference in mortality between males and females, similar to an earlier study conducted in Uganda [28]. Even in the interventional CryptoDex trial in Uganda and Asia, a similar trend of sub-optimal long-term survival was observed, with mortality of 60% at 2 years among HIV patients with CM [29,30]. Conversely, an earlier study in Uganda observed a 5-year survival rate of 42% among 189 CM patients which is higher compared to our study [11].…”
Section: Plos Onesupporting
confidence: 87%
“…This study found that low GCS (< 15/15), focal neurological signs, delay in CM diagnosis, and FLU monotherapy were significant predictors of mortality for CM in PLWH. Low GCS, defined as a score < 15/15 or a reduced level of consciousness, was supported as a mortality predictor by studies looking at both short-term and long-term mortality predictors which applied cox regression models to establish associations ( 57 , 63 ). Another study done in Uganda linked low GCS to seizure occurrence and these were associated with higher 10-week mortality ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, these anti-inflammatory drugs function by suppressing the migration of neutrophils and decreasing lymphocyte colony proliferation (27). The potential of dexamethasone as a treatment strategy during cryptococcal infection was investigated in a clinical trial but was prematurely concluded because of adverse effects and increased mortality (28, 29); however, corticosteroids have been used successfully to treat CME-associated inflammatory disorders such as postinfectious inflammatory response syndrome and immune reconstitution inflammatory syndrome (21). Given the robust pro-inflammatory immune response observed in the pdr6 Δ-infected mice, we hypothesized dexamethasone treatment would dampen or knock down the aggressive Th1 response resulting in fungal clearance and improved survival.…”
Section: Resultsmentioning
confidence: 99%